ANALYSIS OF EFFICIENCY, EFFECTIVENESS, POTENTIAL, AND CONTRIBUTION OF P2 PBB REVENUE TO PAD REGENCY BLITAR 2016-2021 - Oktavia, Siska Putri; Lutfllah, Novrida Qudsi; Ari Kamayanti (Accounting Profession Journal (APAJI), 2023)
This research is aimed to analyze management of Rural and Urban Land and Building Tax (PBB P2) in Blitar Regency in 2016-2021. Qualitative research with descriptive analysis. Primary and secondary data were obtained through semistructured interview, documentation and observation. The results indicate that efficiency was 4.5% criterion very efficient. Effectiveness 106% was criterion very effective. The proportion ratio was 3.35 criterion prime criteria. The growth ratio was 0.12 in potential. Contribution was 10% criterion very poor category. Obstacle factors were human resources, budget, facilities and infrastructure, covid 19. Supporting factors were leadership, data updating, e-pbb, regulatory factors, taxpayer awareness, targeting.